Assessment of Turnover Intentions and Employee Commitment among Teachers of the Ghana Education Service in the Bolgatanga Municipality - Afebia, C.A (University of Ghana, 2016)
Teacher turnover is a phenomenon that has assumed a global dimension, requiring more attention from all stakeholders in Ghana. This study examined the factors that influence turnover intentions, the effects of turnover intentions on teachers’ commitment to Ghana Education Service (GES) and the teaching profession and how to reduce turnover intentions among teachers in the Bolgatanga Municipality. The study adopted a survey research design. A total sample of two hundred and fifty four respondents were recruited from public basic and senior high schools in the Bolgatanga Municipality. A structured questionnaire was developed to collect the data. A comparative analysis was conducted between male and female teachers in respect of their turnover intentions while similar analysis was conducted between senior and basic schools to assess the effects of turnover intentions on teachers. Data was analyzed using version 20 of the Predictive Analytics Software (PASW), formerly SPSS. The findings indicate that more male teachers than female teachers view teaching as a stepping stone to other professions. Thus, while male teachers are more likely to quit teaching, female teachers in the Municipality are less likely to quit. Low salaries, delay in promotions, and the lack of incentives were ranked as factors most likely to influence turnover intentions. Affective commitment was found to be higher than normative and continuance commitment with respect to occupational commitment to the profession. This means teachers in the Municipality showed obligation, loyalty to the teaching profession and shared in the norms of the profession thus, making teachers in the Municipality to record low turnover intentions. With regard to organizational commitment, normative and continuance commitment correlated high with teacher’s commitment to GES as an organization. The findings indicate that teachers demonstrated attachment to the GES because of obligation and loyalty and expressed reluctance to leave for pragmatic reasons including; lack of alternative jobs, study leave and retirement benefits associated with GES. The findings suggest that in order to reduce turnover intentions among teachers; increased salaries, payment of full salary arrears, accommodation allowances, and medical allowances would have to be paid to teachers. The Fair Wages and Salaries Commission, the Controller and Accountant general department have been identified as key stakeholders to work to reduce turnover intentions. It is recommended that the Municipal Directorate should court Non-Governmental Organisations in Education and private individuals as well as philanthropist to consider establishing incentive packages to reward hardworking teachers in the Municipality. It is further recommended that government must proactively address the concerns of teachers especially those that relate to compensation. Also, government must not seek to justify its inability to address the concerns of teachers based on their numbers. If this trend is not checked by successive governments, more trained teachers would consider quitting the teaching profession.
Thesis(MPHIL)-University of Ghana, 2016
Keywords: Turnover Intentions; Employee Commitment; Ghana Education Service; Bolgatanga Municipality